2004
DOI: 10.1002/ijc.20042
|View full text |Cite
|
Sign up to set email alerts
|

p53, p16 and cyclin D1: Molecular determinants of radiotherapy treatment response in oral carcinoma

Abstract: Management of oral cancer by radiotherapy has witnessed promising advances in the past few years, with patient-tailored radio fractionation regimens. Different fractionation schedules, conventional and altered regimes, have been used in curative radiotherapy. Although contribution of biological markers on radio response has been evaluated, its unique influence on various radio fractionation schemes has not been accounted so far. Our study analyses a set of proteins that previously demonstrated radio response i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 34 publications
(30 reference statements)
5
36
1
Order By: Relevance
“…22 Our previous report also demonstrated that p16 and cyclin D1 were significant biological markers to assess the radioresponse in oral cancer patients. 9 Cyclin D1 and p16 predicted the survival of the patients comparatively stronger than any of the conventional clinicopathological prognostic markers examined. Therefore, subgrouping the patients based on the molecular phenotype of cyclin D1 and p16, we could identify groups of patients with bad prognosis, and this might be of clinical utility in designing treatment modalities.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…22 Our previous report also demonstrated that p16 and cyclin D1 were significant biological markers to assess the radioresponse in oral cancer patients. 9 Cyclin D1 and p16 predicted the survival of the patients comparatively stronger than any of the conventional clinicopathological prognostic markers examined. Therefore, subgrouping the patients based on the molecular phenotype of cyclin D1 and p16, we could identify groups of patients with bad prognosis, and this might be of clinical utility in designing treatment modalities.…”
Section: Discussionmentioning
confidence: 86%
“…We had reported earlier that p53 overexpression detected by mutant-specific Pab240 can independently predict the local treatment failure in conventional fractionation of radiotherapy protocol and not in altered fractionation schedule. 9 Conventional fractionation is expected to activate selectively p53-mediated apoptotic pathway in the tumour cell. Hence, patients with mutant-specific p53 overexpression should be considered for other treatment modalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were published by others. 25,37 Jayasurya et al further differentiated oral squamous cell carcinoma treated by normal from altered fractionation. Loss of p16 expression combined with cyclin D1 overexpression correlated to worse prognosis in the 90 tumors treated by altered fractionation only.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we can compare the influence of p16 expression on overall survival in both treatment groups. Reports on prognosis of HPV induced p16 positive OPSCC including tumor collectives treated by different treatment modalities such as surgery, 26,37 RT, 37 RCT 25,40 or OPSCC treated by various, but summarized modalities. 15,20,21,24,34,35,38,39 In addition, our single-institutional study requires validation in large prospective trials prior to implementation of p16 as a potential prognostic marker in OPSCC.…”
Section: Discussionmentioning
confidence: 99%